Análise do cenário dos resíduos de construção e demolição no município de Goianésia do Pará - FERREIRA, Alex Jorge Gaia (2024)
The construction industry generates large amounts of waste, with estimates exceeding 10 billion tons of construction and demolition waste (CDW) per year (Lins et al. 2023). This situation is also reflected locally, as in the municipality of Goianésia do Pará, which faces challenges related to the management of this waste. This article aims to analyze the CDW scenario in the municipality of Goianésia do Pará, State of Pará, focusing on the estimation of waste generation. To this end, an interview was conducted with a representative from SEMA, and visits were made to waste disposal sites. The results indicate an estimated volume of 4,196.72 tons/year of CDW generated in the municipality. Among the most frequent types of CDW, Class A and B stand out, which are recyclable. The highest concentration of disposal sites is located in the Santo Amaro and Floresta neighborhoods. The need for public policies aimed at the reuse and recycling of this waste is evident.